2023
DOI: 10.1002/mawe.202200205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamina orientation, crack severity, and fillers on dynamic parameters of hybrid composite cantilever beam with double transverse cracks

Abstract: Modern-day research in composite material development primarily focuses on tailoring combinations by proportions of constituent materials and monitoring the changes in their targeted properties. In line with this trend, a new class of glass fiber reinforced polymer hybrid composite beam of size 600 mm × 50 mm × 6 mm is fabricated by adding graphene (average particle size:10 μm), and flyash (average particle size: 60 μm). The dynamic behavior of the hybrid beam by introducing two transverse cracks at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…where: 𝑘 = 10; 𝑟 , 𝑟 , 𝑟 are relevant parameters, this paper takes 𝑟 = 𝑟 , 𝑟 = 12𝑟 ; 𝜇 = 0.25 is the rock Poisson's ratio [35][36][37][38]. By calculating the above formula and referring to existing literature [39][40][41], the peak value of the blasting load is less than 20 MPa, as shown in Fig. 5.…”
Section: Blast Loading Methodsmentioning
confidence: 99%
“…where: 𝑘 = 10; 𝑟 , 𝑟 , 𝑟 are relevant parameters, this paper takes 𝑟 = 𝑟 , 𝑟 = 12𝑟 ; 𝜇 = 0.25 is the rock Poisson's ratio [35][36][37][38]. By calculating the above formula and referring to existing literature [39][40][41], the peak value of the blasting load is less than 20 MPa, as shown in Fig. 5.…”
Section: Blast Loading Methodsmentioning
confidence: 99%
“…Sahoo S. et al designed a hybrid beam made of glass epoxy composite material mixed with fly ash and graphene. Simulated experimental results showed that the designed material had significantly improved stiffness compared to traditional materials [7][8]. Compared to traditional methods, LC technology has wider selectivity, smaller thermal deformation, higher coating density, strong adaptability and flexibility, and shorter cost and cycle.…”
Section: Introductionmentioning
confidence: 98%
“…While research on regular beams covered with functionally graded materials is rare, there are no studies on the natural frequencies of irregular non-uniform beams, coated with functionally graded materials [18][19][20][21][22][23][24]. Some research is done on nano beams and coated beams as well [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%